Contenido de proteína, lisina y potasio en grano de trigo en función de época de siembra y cultivar - Barriga B., Patricio; Fuentealba A., Juan; Manquián T., Nimia (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Four cultivars of spring wheat (Triticum aestivum L.) were grown at four dates of planting in Valivia, Chile, to study the effects on total protein content, lysine and potassium of wheat grain. The results indicated that only total protein content was affected by dates of planting and cultivars. Protein content of the showed an inverse relationship with the lysine content in the protein (y = 6,76 -0,42 x, r = -0,774**). However, a positive relationship was found between the lysine content in the protein and the potassium content of the grain (y = 14,800 x - 3,701; r = 0,552*). There was not significative correlation between protein content and the potassium content